2010
DOI: 10.1016/j.jsat.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A randomized pilot study of the Engaging Moms Program for family drug court

Abstract: In response to the need for effective drug court interventions, the effectiveness of the Engaging Moms Program (EMP) versus intensive case management services (ICMS) on multiple outcomes for mothers enrolled in family drug court was investigated. In this intent-to-treat study, mothers (N = 62) were randomly assigned to either usual drug court care or the Engaging Moms drug court program. Mothers were assessed at intake, and 3, 6, 12, and 18 months following intake. Results indicated that at 18 months post drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 43 publications
1
106
0
Order By: Relevance
“…2. Of the 20 different intervention programs focusing on maltreatment outcomes only five (25 %) programs effectively prevented or reduced [54]; SOS, [14]; Multisystemic Therapy for Child Abuse and Neglect [MST-CAN], [30]; and PCIT with and without individualized services, [20]). PCIT in its original form [20] yielded the largest effect size (d = 1.09).…”
Section: Which Interventions Are Most Effective?mentioning
confidence: 99%
“…2. Of the 20 different intervention programs focusing on maltreatment outcomes only five (25 %) programs effectively prevented or reduced [54]; SOS, [14]; Multisystemic Therapy for Child Abuse and Neglect [MST-CAN], [30]; and PCIT with and without individualized services, [20]). PCIT in its original form [20] yielded the largest effect size (d = 1.09).…”
Section: Which Interventions Are Most Effective?mentioning
confidence: 99%
“…Of the two, there is more evidence that FDTCs increase reunification rates; nine studies found an increase in reunification for participants (Ashford, 2004;Boles, Young, Moore, & DiPirro-Beard, 2007;Burrus, Mackin, & Finigan, 2011;Chuang, Moore, Barrett, & Young, 2012;Dakof et al, 2010;Gifford, Eldred, Vernerey, & Sloan, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2009;Green, Rockhill, & Furrer, 2007b;Worcel, Furrer, Green, Burrus, & Finigan, 2008). Several studies found reduced time spent in foster care for children of participants (Bruns, Pullmann, Weathers, Wirschem, & Murphy, 2012;Burrus et al, 2011;Gifford et al, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2007a;Worcel et al, 2008), although one study reported longer stays (Chuang et al, 2012) and another found the effect varied by court (Green et al, 2009).…”
Section: Family Drug Treatment Courtsmentioning
confidence: 99%
“…One small pilot study found evidence of lower probability of termination of parental rights following parental FDTC involvement (Dakof et al, 2010). However, these findings mainly come from single court studies serving a single county (e.g., Ashford, 2004; Boles, Young, Moore, & DiPirro-Beard, 2007; Bruns et al, 2012; Chuang et al, 2012), and were based on relatively small samples (e.g., Dakof et al, 2010; Green, Furrer, Worcel, Burrus, & Finigan, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the National Survey of Adolescent Well-Being found no short-term positive or harmful effects of home removal on cognitive functioning or behavior problems (Berger, Bruch, Johnson, James, & Rubin, 2009). Empirical studies have documented that FDTC participants are more likely than comparison groups to be reunified with their children (see Table 1) or less likely to have their parental rights terminated (Dakof et al, 2010). …”
Section: Introductionmentioning
confidence: 99%